Peningkatan Kemampuan Mengenal Huruf Melalui Permainan Kartu Huruf Pada Kelompok B TK Negeri Pembina Sape - Fitri Rahayu; Ihlas Ihlas; Ade S. Anhar (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2024)
This research aims to explore how the use of letter card games can enhance letter recognition skills among children in group B of TK Negeri Pembina Sape. The study employs an action research approach with 28 Early Childhood Education (ECE) children from TK Negeri Pembina Satu, comprising 12 boys and 16 girls, as the research subjects. The research focuses on improving letter recognition skills through the utilization of letter card games. Data collection involves observation and documentation using a checklist observation instrument. Data analysis is conducted through quantitative descriptive techniques. The results indicate that the use of letter card games is effective in improving letter recognition skills among group B children at TK Negeri Pembina Satu. The percentage of letter recognition skills increased from an initial condition of 35.85% to 61.11% in Cycle I, and further increased to 83.73% in Cycle II. The percentage increase from Pre-cycle to Cycle I is 25.27%, while the increase from Cycle I to Cycle II is 22.62%.